Complete Metamorphosis in Manduca sexta Involves Specific Changes in DNA Methylation Patterns - Gegner, Jasmin; Vogel, Heiko; Billion, André; Förster, Frank; Vilcinskas, Andreas (Frontiers in Ecology and Evolution, 2021)
The transition between morphologically distinct phenotypes during complete metamorphosis in holometabolous insects is accompanied by fundamental transcriptional reprogramming. Using the tobacco hornworm (Manduca sexta), a powerful model for the analysis of insect evolution and development, we conducted a genome-wide comparative analysis of gene expression and DNA methylation in caterpillars and adults to determine whether complete metamorphosis has an epigenetic basis in this species. Bisulfite sequencing indicated a generally low level of DNA methylation with a unimodal CpGO/E distribution. Expression analysis revealed that 24 % of all known M. sexta genes (3729) were upregulated in last-instar larvae relative to the adult moth, whereas 26 % (4077) were downregulated. We also identified 4946 loci and 4960 regions showing stage-specific differential methylation. Interestingly, genes encoding histone acetyltransferases and histone deacetylases were differentially methylated in the larvae and adults, indicating there is crosstalk between different epigenetic mechanisms. The distinct sets of methylated genes in M. sexta larvae and adults suggest that complete metamorphosis involves epigenetic modifications associated with profound transcriptional reprogramming, involving approximately half of all the genes in this species.